Hubungan Pengetahuan Caregiver Informal Tentang Safety Home Dengan Upaya Pencegahan Jatuh Pada Lansia - Regita Yuliana Bete; Febrina Secsaria Handini; Monika Luhung (Jurnal Riset Kesehatan Nasional, 2026)
Abstract Elderly people are vulnerable to falls, often due to declining strength and poor housing conditions. An informal caregiver must understand how to create a safe home environment. A safe home can contribute greatly to preventing falls. The purpose of this research is to analyze the relationship between informal caregiver knowledge about safety home and efforts to prevent falls in the elderly in RW 01 Sukoharjo Village. The study used a non-experimental descriptive quantitative approach with cross sectional data collection. The research site was RW 01 Sukoharjo Village with a sample size of 50 people taken with total sampling technique. The instruments used were knowledge questionnaire and HOMEFAST modified questionnaire which were tested valid and reliable. Data analysis used Spearman Rank test. The majority of 90% had good knowledge and 82% had good prevention efforts. There is a relationship between informal caregiver knowledge and fall prevention efforts (P-Value = 0.000). This study confirms that knowledge about home safety and good prevention efforts from informal caregivers contribute significantly to the prevention of elderly fall incidents at home. Keywords: Knowledge, Informal Caregiver, Safety Home, Fall, Fall Prevention, Elderly